Experimental analysis of energy conversion and noise suppression mechanism using polyvinylidene difluoride piezoelectric element. (October 2022) - Patil, Avadhut Tukaram; Mandale, Maruti Bhagwan
Energy conversion and conservation techniques are well known for different natural sources but one of the common sources of energy that stays unutilized in the environment is sound energy. The noise around us is a form of unutilized energy. The acoustic energy can be utilized to produce electrical energy. In this article, the testing of the acoustic energy conversion technique is performed. Here the acoustic low amplitude pressure waves generated by the buzzer ringer have impinged over the surface of PVDF (Polyvinylidene Difluoride) Piezoelectric element which has the capability to vibrate after sound impingement. Here the experimental results are taken in the frequency range of 400 Hz to 1300 Hz, in which the highest response occurred at a frequency of 1000 Hz and 91.9 dB, which is +/−50 mV and the maximum Vrms (Voltage; root mean square) is 35.35 mV by the single piezoelectric unit. The performance of an array of resonating tube chambers as an enclosure to the noise source has been observed to accomplish noise reduction. Then the array pattern arrangement of this entire system has been discussed with the predictions of the output voltage.